CercetAfri Privind Utilizarea Anticorpilor Monoclonali Azi Policlonali AZn EvidenAierea Celulelor Stem Umane Neuronale AZn Creierul Fetal Ovin (Global Journal of Science Frontier Research, 2013)
A stem cell has two main properties: long-term capacity autoreînnoire without senescence and pluripotenţă and ability to differentiate into one or more specialized cell types. These cells can provide an inexhaustible source of cells for transplantation. Totipotente stem cells that have the ability to generate all types of tissue plays a critical role in human development, providing material for the development of all tissues and organs in the embryo and in all extra embryonic tissues.
Keywords: development; providing material for the development greater plasticity